Non-invasive management of severe chlamydia psittaci pneumonia presenting with hypoxemia and diarrhea: a case report - Xuanqi Liu; Dongmei Hu; Jieyi Tan; Yingdian Yu (Frontiers in Medicine, 2026)
This case report describes a rare presentation of severe Chlamydia psittaci pneumonia in a 43-year-old female patient with prominent hypoxemia and gastrointestinal symptoms, and evaluates the efficacy of standardized non-invasive integrated management for critically ill patients with this atypical phenotype. The patient was admitted with lumbago, persistent high fever, progressive dyspnea, severe hypoxemia, and intractable non-bloody watery diarrhea. Chest computed tomography (CT) revealed extensive bilateral pulmonary ground-glass opacities and consolidation. Rapid and precise etiological diagnosis was achieved via targeted metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF), which identified high-load Chlamydia psittaci infection, with 227,155 normalized reads and a genomic coverage of 98.6%. Comprehensive non-invasive multidisciplinary management was implemented throughout the disease course, including high-flow nasal cannula (HFNC) oxygen therapy, dual anti-infective therapy with omadacycline combined with levofloxacin, symptomatic supportive care, and standardized stepwise early rehabilitation training. Dynamic monitoring of clinical and laboratory indicators showed a gradual and sustained decline in inflammatory biomarkers (C-reactive protein,procalcitonin, interleukin-6),accompanied by progressive absorption of pulmonary lesions and recovery of respiratory function. The patient avoided invasive mechanical ventilation throughout hospitalization, was successfully weaned from HFNC on day 14 of admission, and achieved completeclinical, laboratory and radiological recovery at the 1-month follow-up. This case conforms to the CARE (CAse REports) reporting guidelines. It highlights that severe psittacosis pneumonia can present with atypical dominant manifestations of combined hypoxemia and severe gastrointestinal diarrhea, which is easily misdiagnosed clinically. Targeted mNGS enables rapid etiological confirmation of atypical severe psittacosis, and individualized non-invasive integrated management can achieve favorable prognosis in eligible critically ill patients, providing a valuable clinical reference for the standardized diagnosis and treatment of similar rare cases.